Burma : - Keylly, Talbot (J. B. Millet Co., 1910)
This book introduce about Rangoon, amenities of Rangoon, across the Yomas to Taungdwingyi, in a burmese market tơn, jungle life at Kokogon, through the forest to Pyinmana. One thousand miles up the irawaddy...